2012
DOI: 10.1039/c2an35700c
|View full text |Cite
|
Sign up to set email alerts
|

BSA-templated MnO2 nanoparticles as both peroxidase and oxidase mimics

Abstract: Inorganic nanomaterials that mimic enzymes are fascinating as they potentially have improved properties relative to native enzymes, such as greater resistance to extremes of pH and temperature and lower sensitivity to proteases. Although many artificial enzymes have been investigated, searching for highly-efficient and stable catalysts is still of great interest. In this paper, we first demonstrated that bovine serum albumin (BSA)-stabilized MnO(2) nanoparticles (NPs) exhibited highly peroxidase-, oxidase-, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
193
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(212 citation statements)
references
References 34 publications
13
193
1
5
Order By: Relevance
“…65 Taken together, due to the synergistic effect of specific surface property, composition and nano-structure, the catalytic activity of Au@Ag heterogeneous NRs at pH 6.5 differed from that of other similar nanomaterials, such as positively charged PDDA modified Au@Pt core/shell NRs (pH 4.5) or negatively charged PSS modified Au@Pt core/shell NRs (pH 4.5), 46 positively charged CTAB-modified Au@Pt core/shell NRs (pH 4.5), 40 concentration was detected in the neutral condition, which was different from other peroxidase-mimetic materials used in acidic conditions reported so far. [23][24]26 In addition, this performance can also be comparable with our recent results on the detection of H 2 O 2 by using Au@Ag heterogeneous NRs-based electrochemical sensor . 59 Thus, it is beneficial to directly detect the real samples (such as serum and drink) without adjusting the pH value.…”
Section: Effect Of the Nano-structure On Peroxidase-like Activity Ofsupporting
confidence: 86%
“…65 Taken together, due to the synergistic effect of specific surface property, composition and nano-structure, the catalytic activity of Au@Ag heterogeneous NRs at pH 6.5 differed from that of other similar nanomaterials, such as positively charged PDDA modified Au@Pt core/shell NRs (pH 4.5) or negatively charged PSS modified Au@Pt core/shell NRs (pH 4.5), 46 positively charged CTAB-modified Au@Pt core/shell NRs (pH 4.5), 40 concentration was detected in the neutral condition, which was different from other peroxidase-mimetic materials used in acidic conditions reported so far. [23][24]26 In addition, this performance can also be comparable with our recent results on the detection of H 2 O 2 by using Au@Ag heterogeneous NRs-based electrochemical sensor . 59 Thus, it is beneficial to directly detect the real samples (such as serum and drink) without adjusting the pH value.…”
Section: Effect Of the Nano-structure On Peroxidase-like Activity Ofsupporting
confidence: 86%
“…4C and D, the slopes of the lines are parallel, indicating a ping-pong mechanism [6,34] and implying that the CuInS 2 nanocrystals bind and react with the first substrate and then release the first product before reacting with the second substrate.…”
Section: Methodsmentioning
confidence: 92%
“…Recently, nanomaterials-based artificial enzyme mimetics with high catalytic properties and a wide range of practical applications are becoming a significant field for different purposes. Various nanomaterials including metallic oxide (Fe 3 O 4 nanoparticles [3], CeO 2 nanoparticles [4], Co 3 O 4 nanoparticles [5], MnO 2 nanoparticles [6], V 2 O 5 nanowires [7], CuO nanoparticles [8]), FeS nanoparticles [9], carbon-based nanomaterials (carbon nanotube [10], helical carbon nanotube [11], graphene [12], graphene oxide [13], carbon nanodots [14]), metallic and bimetallic alloy nanostructures (Au nanoparticles [15], Pt nanoparticles [16], Au and Cu nanoclusters [17,18], Au/Ag nanoparticles [19] Au/Pt nanoparticles [20]), and layered double hydroxide [21] have been applied in the biochemical applications as enzyme mimetics. However, there is much demand to explore the stable, dispersive, and easily prepared nanomaterials with good catalytic properties as peroxidase mimetics in the practical application.…”
Section: Introductionmentioning
confidence: 99%
“…nanosheets, nanospheres, nano-sticks, nano-complexes and nanowires) have also been studied to determine their oxidase and peroxidase and catalase mimicking activity [60]. Liu et al showed that BSA-stabilized Mno þ2 can be used instead of HRP enzyme and in the detection of goat anti-human in immunoassay technic as a colorimetric application [60].…”
Section: Manganese Dioxide As Oxidasementioning
confidence: 98%
“…Experimental studies demonstrated that the H 2 O 2 -activating ability of Fe 3 O 4 MNPs is not so close to the removal of hydrogen superoxide, but it may modify by increasing the H 2 O 2 -activating ability of Fe 3 O 4 MNPs of refractory organic pollutants from wastewaters [60]. H 2 O 2 detection is useful in many fields such as biology, medicine, environmental protection and the food industry [61].…”
Section: Iron Oxide-based Nanomaterialsmentioning
confidence: 99%